Enhancing Agricultural Development: Innovations and Strategies for Sustainable Growth - Rochman, Abdul (International Journal of Social Science, Education, Communication and Economics, 2025)
Agricultural development is pivotal for economic growth, food security, and poverty alleviation, particularly in developing countries. This paper explores the factors driving agricultural development, innovative practices, and strategic frameworks essential for sustainable growth. The research highlights the interconnections between technology adoption, policy frameworks, and market access, emphasizing the need for an inclusive approach that addresses the needs of smallholder farmers who constitute a significant portion of the agricultural workforce. Through a comprehensive review of current literature, case studies, and empirical data analysis, the study identifies key challenges facing the agricultural sector, such as climate change, land degradation, and access to resources. Innovations in agricultural practices, including precision farming, biotechnology, and sustainable land management, are discussed as vital components for enhancing productivity and resilience. Additionally, the role of policy interventions in promoting agricultural research and development, facilitating access to markets, and ensuring food security is critically assessed. The findings indicate that fostering collaboration among stakeholders—governments, private sectors, and local communities—is crucial for achieving sustainable agricultural development. Ultimately, this research aims to provide actionable insights and policy recommendations that promote agricultural innovation and improve the livelihoods of farmers, thereby contributing to enhanced food security and economic prosperity.